2006
DOI: 10.1021/jp056198x
|View full text |Cite
|
Sign up to set email alerts
|

Does Magnetic Treatment of Water Change Its Properties?

Abstract: Some properties and functions of water treated under magnetic field were examined. No change in properties of pure water distilled from ultrapure water in vacuum was observed by magnetic treatment. However, when the same magnetic treatment was carried out after the distilled water was exposed to O2, water properties such as vibration modes and electrolytic potential were changed. The degree of magnetic treatment effect on water was quantitatively evaluated by contact angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 18 publications
5
76
0
1
Order By: Relevance
“…Finding that this angle is slightly lower than in the untreated water, which indicates a decrease in hydrophobicity. The above is in accordance with Otsuka and Ozeki (2006), results who observed that the contact angle of droplets of magnetized water was lower than that of untreated water, measured on a copper surface. Other authors (Amiri and Dadkhah, 2006 ;Cai et al, 2009 ;Toledo et al, 2013 andHasaani et al, 2015) have verified a reduction in surface tension under different experimental conditions.…”
Section: Introductionsupporting
confidence: 93%
“…Finding that this angle is slightly lower than in the untreated water, which indicates a decrease in hydrophobicity. The above is in accordance with Otsuka and Ozeki (2006), results who observed that the contact angle of droplets of magnetized water was lower than that of untreated water, measured on a copper surface. Other authors (Amiri and Dadkhah, 2006 ;Cai et al, 2009 ;Toledo et al, 2013 andHasaani et al, 2015) have verified a reduction in surface tension under different experimental conditions.…”
Section: Introductionsupporting
confidence: 93%
“…It is clear now, that the ionization of both salts increases by elevating the pH value. This result is linked to other works which declare that, the magnetic treatment of water has been reported to change some of the physical and chemical properties of water, mainly hydrogen bonding, polarity, surface tension, conductivity, pH and solubility of salts (21)(22)(23)(24) .…”
supporting
confidence: 77%
“…Importantly, its salts are known to be a major contributor to the osmotic potential of cells and tissues [22]. Many researchers have shown that magnetic treatment changes the physical parameters of water such as surface tension [23], diffusion velocity [19], salts' solubility [24], vibration modes and electrolytic potential [25]. Some of these parameters could impact osmotic potential and therefore nutrient uptake.…”
Section: Resultsmentioning
confidence: 99%